2006
DOI: 10.1002/jgm.928
|View full text |Cite
|
Sign up to set email alerts
|

PhiC31 integrase mediates integration in cultured synovial cells and enhances gene expression in rabbit joints

Abstract: The ability of phiC31 integrase to facilitate genomic integration in synovial cells and increase transgene expression in the rabbit synovium suggests that, in combination with more efficient DNA delivery methods, this integrase system could be beneficial for treatment of rheumatoid arthritis and other joint disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
1
26
1
1
Order By: Relevance
“…We observed nearly 40-fold higher levels of luciferase expression in the mNPCs modified with ϕC31 integrase as compared to those without at 8 weeks after nucleofection. The stable expression of the transgene has been attributed to the ability of ϕC31 integrase to mediate integration of the gene into host chromosomes (Groth et al, 2000;Thyagarajan et al, 2001;Olivares et al, 2002;Ortiz-Urda et al, 2002;Quenneville et al, 2004;Chalberg et al, 2005;Ishikawa et al, 2006;Bertoni et al, 2006;Keravala et al, 2006;Portlock et al, 2006). We obtained PCR evidence for integration of the luciferase plasmid at mpsL1, a known genomic hot-spot utilized by ϕC31 integrase (Olivares et al, 2002;Bertoni et al, 2006;Portlock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We observed nearly 40-fold higher levels of luciferase expression in the mNPCs modified with ϕC31 integrase as compared to those without at 8 weeks after nucleofection. The stable expression of the transgene has been attributed to the ability of ϕC31 integrase to mediate integration of the gene into host chromosomes (Groth et al, 2000;Thyagarajan et al, 2001;Olivares et al, 2002;Ortiz-Urda et al, 2002;Quenneville et al, 2004;Chalberg et al, 2005;Ishikawa et al, 2006;Bertoni et al, 2006;Keravala et al, 2006;Portlock et al, 2006). We obtained PCR evidence for integration of the luciferase plasmid at mpsL1, a known genomic hot-spot utilized by ϕC31 integrase (Olivares et al, 2002;Bertoni et al, 2006;Portlock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo-attP sites have traits similar to those of human, mouse, rat, and Drosophila. 5,7,10) By using the ÈC31 integrase gene delivering system, elevated integration frequency and effective gene expression can be effected in sheep fibroblasts. Furthermore, we have obtained large numbers of integrase-mediated transgenic embryos by somatic-cell nuclear transfer (data not shown).…”
Section: èC31 Integrase Enhanced Integration Efficiencymentioning
confidence: 99%
“…These have been identified in the genome of human, mouse, rat, rabbit, and Drosophila. [6][7][8][9] Furthermore, unlike the widely used Cre and FLP recombinases, which can catalyze both integration and excision, ÈC31 integrase-mediated integration is unidirectional. This makes the ÈC31 integrase system preferable for transgene insertion.…”
mentioning
confidence: 99%
“…According to the published data (Groth et al, 2004;Chalberg et al, 2005Chalberg et al, , 2006Keravala et al, 2006;Ma et al, 2006;Ehrhardt et al, 2007; Qu et al, 2012), the sequences we retrieved around the pseudo attP sites were about 200 bp. As a control, 97 random sequences corresponding to these species were similarly analyzed by motif finder software.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…It has been reported that the integrations induced by fC31 integrase support high-level and long-term expression of foreign genes (Ortiz-Urda et al, 2002Quenneville et al, 2004;Held et al, 2005;Keravala et al, 2006;Ou et al, 2009). We observed long-term expression up to 30 days for GFP integrated at the pseudo attP sites of C. hircus fibroblast cells, Figure 3A.…”
Section: Gfp Expression In Different Integration Sitesmentioning
confidence: 99%